The biological roots of the sex-frailty paradox - Beatrice Arosio; Anna Picca (Experimental Gerontology)
Aging is a dynamic process that requires a continuous response and adaptation to internal and external stimuli over the life course. This eventually results in people aging differently and women aging differently than men. The “gender paradox” describes how women experience greater longevity than men, although linked with higher rates of disability and poor health status.Recently, the concept of frailty has been incorporated into this paradox giving rise to the “sex-frailty paradox” which describes how women are frailer because they manifest worse health status but, at the same time, appear less susceptible to death than men of the same age. However, very little is known about the biological roots of this sex-related difference in frailty.Inflamm-aging, the chronic low-grade inflammatory state associated with age, plays a key pathophysiological role in several age-related diseases/conditions, including Alzheimer's disease (AD), for which women have a higher lifetime risk than men. Interestingly, inflamm-aging develops at a different rate in women compared to men, with features that could play a critical role in the development of AD in women.According to this view, a continuum between aging and age-related diseases that probably lacks clear boundaries can be envisioned in which several shared biological mechanisms that progress at different pace may lead to different aging trajectories in women than in men. It, therefore, becomes urgent to consider a holistic approach in the study of aging, and decline it from a gender medicine perspective also considering the biological roots of the sex-frailty paradox.